Tool for the analysis of CO₂ emissions on asphalt pavement roads: case study in Baja California, Mexico. - Flores Ruiz , Juan Diego (2024)
The objective of this research was to develop and implement a tool to calculate carbon dioxide emissions generated during the use and end-of-life phases of a section of asphalt pavement, considering as a case study a section of the Mexicali–San Felipe road in Baja California, Mexico, with an analysis period of 35 years. The methodology employed consisted of applying the principles of Life Cycle Assessment (LCA) established in the ISO 14040 and 14044 standards, collecting specific data such as vehicle traffic, pavement geometry and structure, and the fuel efficiency and consumption of the machinery used to remove and transport the asphalt material. The results showed that during the study period, the use phase generated approximately 147.56 tonnes of CO₂ associated with projected vehicle traffic, reflecting a cumulative impact from the continuous use of the road, while the end-of-life phase contributed 61.33 tonnes of CO₂ generated by the removal and disposal of damaged materials (construction waste). Therefore, it is concluded that both stages contribute significantly to the total impact of the pavement and should be incorporated into future LCA studies to obtain a more accurate environmental assessment. In this sense, the proposed tool is practical, adaptable, and replicable, providing support for sustainability-oriented decision-making in the design, operation, and rehabilitation of road infrastructure.